2018
DOI: 10.3892/ol.2018.8029
|View full text |Cite
|
Sign up to set email alerts
|

Ex�vivo expansion of human peripheral blood natural killer cells and cytotoxic T lymphocytes from lung cancer patients

Abstract: Lung cancer is the most common type of cancer with the highest cancer-associated mortality rates worldwide, as well as in Vietnam. Numerous studies have demonstrated that higher numbers and higher rate of activity of infiltrating natural killer (NK) cells and cytotoxic T lymphocytes (CTLs) in the tumor are closely correlated with positive prognosis, tumor size decrease and longer survival of lung cancer patients. In the present study, the effectiveness of BINKIT® kit in the ex vivo expansion of NK cells and CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Based on the method we had already developed [26], the immune cell expansion in this cohort study was carried out for three types of cancer (lung, liver, and colon), with a total of 29 sitting across patients. Compared to the literature, our results demonstrated that we were successful in expanding NK cells and CTLs with high average numbers of 2570.1 × 10 6 and 4105.9 × 10 6 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the method we had already developed [26], the immune cell expansion in this cohort study was carried out for three types of cancer (lung, liver, and colon), with a total of 29 sitting across patients. Compared to the literature, our results demonstrated that we were successful in expanding NK cells and CTLs with high average numbers of 2570.1 × 10 6 and 4105.9 × 10 6 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the mean survival time for patients in our study was 18.7 months at 12 months after the transplantation, hence it increased more than twice compared to the estimated survival time at the point of enrollment. From a published report in early 2018 by Hoang et al [26], the mean survival time of seven lung cancer patients were assessed at 17.1 ± 2 months and increased to 19.4 ± 1.7 months after treatment. The 1-year survival rate of our study was 80%, which was higher compared to other reports previously published [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method for immune cell expansion we already published [22]. Briefly, peripheral blood mononuclear cells (PBMNCs) were obtained by density gradient centrifugation using Ficoll-Paque (GE Healthcare, Sweden) and were cultured using BINKIT® (Biotherapy Institute of Japan, Japan) at density of 1 × 10 6 cells/ml in cell initial Medium containing 0.01 KE/ml OK432 (Chugai Pharmaceutical, Japan), 700IU/ml recombinant human IL-2 (rhIL-2) (Chiron, Netherlands), supplemented with 5% of heat-inactivated autologous plasma, cultured in an anti-CD16 monoclonal antibody-immobilized culture flask for NK cell expansion.…”
Section: Isolation and Large -Scale Expansion Of Natural Killer Cells And Cytotoxic T Lymphocytes From Peripheral Bloodmentioning
confidence: 99%